Management of the training process of qualified female hammer throwers - Wrublevsky, E. (New Studies in Athletics, 2005)
The problem of construction of the training process in any sport or discipline is connected in many respects with finding rational periods for the training activities most appropriate for the aims of preparation. To date there is no certain solution to the question of the distribution of training means and their volumes for female hammer throwers. Following the training programmes of other athletes is problematic because the plans do take into account the specific dynamics of the individual`s reaction to specific loadings. It is therefore necessary for the trainer of highly qualified throwers to develop an individualised programme based qualitative and quantitative measurement of the influence of training load (its contents, volume and organisation) on the athlete's organism. In the case of female athletes, this must be strictly co-ordinated with the cyclic changes in the organism, reflected in the psychological condition, the level of serviceability and the display of motor abilities in each phase of ovarian-menstrual cycle. The author concludes by providing six guidelines for developing such a programme.